2006
DOI: 10.1002/uog.2834
|View full text |Cite
|
Sign up to set email alerts
|

Role of bladder neck mobility and urethral closure pressure in predicting outcome of tension‐free vaginal tape (TVT) procedure

Abstract: Objective To investigate how urethral mobility and urethral closure pressure affect the outcome of tensionfree vaginal tape (TVT) insertion for stress incontinence. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 32 publications
4
56
0
1
Order By: Relevance
“…2,4,9 The present study demonstrates that both a vaginal tape too far away and too close to urethra lead to specific sonographic tape appearances and result in reduced success rates and increased complication rates. As we observed that under Valsalva the tape very often acquires a c-shape on US we speculate that c-shape indicates that tension is exerted on the TVT.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…2,4,9 The present study demonstrates that both a vaginal tape too far away and too close to urethra lead to specific sonographic tape appearances and result in reduced success rates and increased complication rates. As we observed that under Valsalva the tape very often acquires a c-shape on US we speculate that c-shape indicates that tension is exerted on the TVT.…”
Section: Discussionmentioning
confidence: 85%
“…Introital US was performed under standardized conditions using a vaginal 5-9 MHz probe of Ultramark HDI C9-5 ICT (ATL, Hamburg, Germany) with pressure-free probe application. 2,3,9 US was performed according to the guidelines for performing lower urinary tract US as part of urogynecologic functional assessment issued by the German Association of Urogynecology. 4 With the patient in the semi-sitting position and a standardized bladder volume of about 300 ml, the US probe was positioned in the area of the vaginal introitus at the external urethral orifice without applying pressure and aligning the axis of the probe to the patient's long body axis (i.e., in coronal and sagittal planes) by one experienced sonographer.…”
Section: Methodsmentioning
confidence: 99%
“…BND parameter is used for direct evaluation of the bladder neck mobility in the vertical axis [10,20]. It is defined as the descent of the point C along the Y-axis during Valsalva maneuver, cough or Kegel's exercise (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to urethral hypermobility, hypomobile urethra with urodynamic features of intrinsic sphincter deficiency (ISD) has been for years regarded as an important risk factor for failure of surgical intervention in SUI patients [6,10]. The reason for this is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Residual urine was measured using a catheter and bladder neck mobility was assessed with perineal ultrasound using a 3.5 MHz curved array probe. 14 Microtip urethral pressure profile measurements were taken in the 45 upright sitting position with the patient at rest using an 8 French Gaeltec 1 double microtip transducer and the transducer opening was orientated in the 3 o'clock position with a withdrawal speed of 1 mm/s. Catheter position was observed during the test to avoid change of orientation.…”
Section: Methodsmentioning
confidence: 99%